2012
DOI: 10.1002/eqe.2202
|View full text |Cite
|
Sign up to set email alerts
|

A model to simulate special concentrically braced frames beyond brace fracture

Abstract: SUMMARY Special concentrically braced frames (SCBFs) are commonly used as the lateral‐load resisting system in buildings. SCBFs primarily sustain large deformation demands through inelastic action in the brace, including compression buckling and tension yielding; secondary yielding may occur in the gusset plate and framing elements. The preferred failure mode is brace fracture. Yielding, buckling, and fracture behavior results in highly nonlinear behavior and accurate analytical modeling of these frames is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 12 publications
2
58
0
2
Order By: Relevance
“…It is assumed that all braces get their limit states at the same time. Many studies have shown that the yielding of all braces in medium-to high-rise SCBFs is almost impossible during the severe ground motions (Roeder et al 2011;Hsiao et al 2013). The mentioned assumption can be somewhat conservative and uneconomic to design the columns, especially in lower stories.…”
Section: Srss Methods For Design Of Columns In Medium To High-rise Scbfsmentioning
confidence: 99%
“…It is assumed that all braces get their limit states at the same time. Many studies have shown that the yielding of all braces in medium-to high-rise SCBFs is almost impossible during the severe ground motions (Roeder et al 2011;Hsiao et al 2013). The mentioned assumption can be somewhat conservative and uneconomic to design the columns, especially in lower stories.…”
Section: Srss Methods For Design Of Columns In Medium To High-rise Scbfsmentioning
confidence: 99%
“…Modelling of the braced frames was done based on the recommendations from different authors [Uriz et al, 2005;Hsiao et al, 2012;Lignos et al, 2013] that have studied the seismic behaviour of special concentrically braced frames:…”
Section: Methodsmentioning
confidence: 99%
“…As far as the modelling of the brace-frame connections is concerned, a typical 40mm thick steel gusset plate is considered. The effect of the aforementioned plate, adopted both for the brace-column and the brace-beam connections, is taken into account though a nonlinear zero-length rotational spring, the properties of which are estimated based on the relationships proposed by Hsiao et al [16,17] as shown in Figure 3. The Steel02 material [18] from the OpenSees [19] library is adopted, using a steel Young's modulus E=210GPa, the expected yield strength f y =1.2•355=426MPa, a post-yield hardening ratio α h =0.3% and parameters that control the transition from elastic to plastic branches, i.e.…”
Section: Step 2: Archetype Buildingsmentioning
confidence: 99%
“…braces), or even through analytical equations for simplicity. For the purpose of this study, ε u is estimated using the equation proposed by Hsiao et al [17] for the maximum strain-range (ε range ). …”
Section: Step 2: Archetype Buildingsmentioning
confidence: 99%